Application-Based Strategic Issue Mapping - Afandi, Syed Agung; Afandi, Muslim; Erdayani, Rizki; Afandi, Nail Hidaya; Lestari, Reski (Paguyuban Panalungtik Sunda (Papanda), 2022)
This activity seeks to enhance the competitiveness of graduates of the State Administration Study Program at Sultan Syarif Kasim Riau State Islamic University in terms of mapping strategic political-government issues by utilizing the Mendeley Application, the Publish or Perish Application, and the Vosviewer Application. This exercise is conducted utilizing the socializing method. This event was held three times within one month, with a total of fifteen participants. According to the poll completed before to this activity, one-third of the participants were still unable to utilize the Mendeley application, and not a single participant knew and understood how to use the Publish or Perish and Vosviewer applications. All participants were able to master utilizing the Mendeley and Publish or Perish applications after completing this task. Additionally, two-thirds of the participants mastered the Vosviewer Application. Overall, it can be inferred that two-thirds of the participants were able to map application-based political-government issues, as doing so needs mastery of the three socialized applications. Keywords: socialization, application-based mapping, mendeley, publish or perish, vosviewer